Building Good Governance in Sustainable Tourism Management in the Riau Islands - Andini, Cindy; Nugraha, Awaludin; Novianti, Evi; Yustikasari, Yustikasari; Pamungkas, Kasno; Hadian, Mohammad Sapari Dwi (Journal of Governance, 2025)
This qualitative study explores the implementation of good governance principles in the management of sustainable tourism in the Riau Islands. The research aims to identify the challenges and opportunities associated with applying good governance in this region, focusing on key areas such as accountability, transparency, legal frameworks, and information dissemination. Data collection was conducted through interviews with government officials, tourism industry stakeholders, and local communities to gain insights into their experiences and perspectives. The findings reveal that while there are significant obstacles, including weak inter-agency coordination and limited community participation, there are also considerable opportunities, such as leveraging public-private partnerships and fostering community-based tourism initiatives. The study concludes by offering recommendations to strengthen governance mechanisms, promote stakeholder collaboration, and enhance the overall sustainability of tourism in the Riau Islands, ensuring balanced benefits for the local economy, environment, and society.